Biology of PEST‐Containing Nuclear Protein: A Potential Molecular Target for Cancer Research - Khan, Nazeer Hussain; Chen, Hao-Jie; Fan, Yuanyuan; Surfaraz, Muhammad; Ahammad, MD.Faysal; Qin, Yang-Zhe; Shahid, Muhammad; Virk, Razia; Jiang, Enshe; Wu, Dong-Dong; Ji, Xin-Ying (Frontiers in Oncology, 2022)
PEST-containing nuclear protein (PCNP), a novel nuclear protein, is involved in vital cellular processes like cell proliferation and mediates tumorigenesis. PCNP is a short-living, small nuclear protein of only 178 amino acids with two remarkable PEST sequences that are rich in proline (P), glutamic acid (E), serine (S), and threonine (T). The current understanding of PCNP reveals that PCNP has the ability to interact with cell cycle regulatory proteins; tumor suppressors (p53 and pRB), and promoters (cyclin E and cyclin D) to determine the fate of tissues to facilitate the process of either apoptosis or cell proliferation. In many preclinical studies, it has been evaluated that PCNP expression has associations with the development and progression of various cancers like neuroblastoma, lung adenocarcinoma, and ovarian cancer. Based on these depicted novel roles of PCNP in cell cycleregulation and of PCNP in tumorigenesis, it is logical to consider PCNP as a potential molecular target for cancer research. The aim of the current communication is to present an update on PCNP research and discussion on the potential role of PCNP in cancer development with challenges and opportunities perspectives. Considering the available evidence as a baseline for our statement, we anticipate that in the future, new research insights will strengthen the aim to develop PCNP-based diagnostic and therapeutic approaches that will move the PCNP from the laboratory to the cancer clinic.